Emotionally Intelligent AI: The Future of Mental Health Care and Emotional Well-being - Ishika; Shreya Pant; Sangeeta Kakkar (Recent Trends in Social Studies, 2025)
With the potential to improve emotional well-being through sophisticated AI systems, emotionally intelligent AI (EI-AI) represents a revolutionary frontier in mental health treatment. EI-AI can recognize, understand, and react to human emotions in real- time by utilizing recent advancements in machine learning, natural language processing, and emotion detection. These features are being used more and more in mental health settings, where chatbots and other AI-driven interventions help with emotional regulation, offer individualized assistance, and make it possible to identify mental health problems early. This review paper examines how EI-AI may transform mental health care by providing immediate emotional support and increasing access to individualized mental health therapies. Additionally, it evaluates the ethical issues and present constraints surrounding the integration of EI-AI in healthcare settings. A comprehensive review has compiled the previous ten years paper results of peer-reviewed research, industry reports, and case studies in the domains of artificial intelligence, mental health, and emotional intelligence. The results of EI-AI applications have shown encouraging outcomes in enhancing emotional control, assisting in the early detection of mental health issues, and easily accessible mental health treatments. It still exists, though, such as difficulties preserving empathy, protecting privacy, and modifying emotion recognition software for various demographics and situations. The broad ramifications of incorporating EI-AI into mental health treatment include improving underprivileged people and offering ongoing mental health monitoring.
Keywords: Emotionally Intelligent AI; Mental health; Personalized Care; emotion recognition; ethical considerations